2018
DOI: 10.1021/acs.chemmater.8b01405
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Solar Water Oxidation by BiVO4 Photoanodes in Basic Media

Abstract: Titanium dioxide (TiO2) deposited by atomic layer deposition (ALD) has been the most commonly used protection layer to enhance chemical and photoelectrochemical stabilities of photoelectrodes. In this study, we report a new electrochemical deposition method that can place a thin, conformal TiO2 coating layer on a photoelectrode. This method takes <1 min and may serve as a practical alternative to ALD for the deposition of a TiO2 layer. The uniform quality of the TiO2 protection layer was confirmed by demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 45 publications
2
62
0
Order By: Relevance
“…Amongst these promising semiconductors are Cu 2 O, 1,2 CuO, 3 Si, [4][5][6][7] III-V semiconductors, 8,9 Cu 2 BaSnS 4 , 10 Cu 2 ZnSnS 4 , 11 and BiVO 4 . 12,13 Additionally, semiconducting buffer layers such as Ga 2 O 3 (ref. 2 and 14) or CdS 3 can be inserted between the photoabsorber and protection layers to increase the built-in voltage, the charge separation and the overall device efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these promising semiconductors are Cu 2 O, 1,2 CuO, 3 Si, [4][5][6][7] III-V semiconductors, 8,9 Cu 2 BaSnS 4 , 10 Cu 2 ZnSnS 4 , 11 and BiVO 4 . 12,13 Additionally, semiconducting buffer layers such as Ga 2 O 3 (ref. 2 and 14) or CdS 3 can be inserted between the photoabsorber and protection layers to increase the built-in voltage, the charge separation and the overall device efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, BpBOD produced a poor bioelectrocatalytic current if it was entrapped in the polydopamine matrix, whereas the DET method based on pyrenebetaine exhibited much better results. In recent years, photoanodes based on BiVO 4 have shown long‐term stability . These findings encourage further development of applications to make use of environmentally friendly, photoactivated PBECs for the generation of electrical energy.…”
Section: Resultsmentioning
confidence: 88%
“…[79][80][81][82] Several thorough review and perspective articles on hematite have been published recently, and the interested reader is referred to these articles for the history and advancements with iron oxide photoanodes. [88][89][90][91][92][93] Pihosh et al have demonstrated impressively high photocurrents using a socalled extremely thin absorber approach, where a thin BiVO 4 layer was coated on WO 3 nanowires, obtaining 6.7 mA cm −2 at an applied bias of 1.23 V versus RHE, which corresponds to about 90% of the theoretical maximum photocurrent value for this material (Figure 5). A major step forward was made with this material when a spray-pyrolysis synthesis method was reported that reproducibly gave currents in the mA cm −2 range, [87] kicking off a flurry of investigation by other researchers.…”
Section: Oxygen Evolutionmentioning
confidence: 97%
“…Also in the 2000s, interest was gaining in a new multinary oxide material, BiVO 4 , as the bandgap was reasonably small for an oxide (≈2.4 eV), and it was composed of earth‐abundant elements. A major step forward was made with this material when a spray‐pyrolysis synthesis method was reported that reproducibly gave currents in the mA cm −2 range, kicking off a flurry of investigation by other researchers . Pihosh et al have demonstrated impressively high photocurrents using a so‐called extremely thin absorber approach, where a thin BiVO 4 layer was coated on WO 3 nanowires, obtaining 6.7 mA cm −2 at an applied bias of 1.23 V versus RHE, which corresponds to about 90% of the theoretical maximum photocurrent value for this material ( Figure 5 ).…”
Section: Photoanodesmentioning
confidence: 99%